A prospective comparative study of efficacy of intralesional bleomycin injection with intralesional 5-FU injection in resistant palmo-plantar warts - Prasoon Sachan; Santosh Kumar Singh; Amit Kumar Pandey; Anil Kumar Gupta; Raj Kumar (Wolters Kluwer Medknow Publications, 2023)
Background: Treating of recalcitrant viral verrucae either individually or in combination is inconvenient and frustrating both for patients and treating physician. There is no treatment, which is 100% effective for warts. Objectives: To compare the use of intralesional 5-flourouracil and intralesional bleomycin with respect to efficacy and side effects in treatment of recalcitrant palmo-plantar verrucae. Materials and Methods: A prospective comparative study was conducted toassess the eeficacy of intralesional bleomycin injection with intralesional 5-Fluoro Uracil (FU) in resistant palmo-plantar warts. Results: Intralesional bleomycin was found to be more efficacious than intralesional 5-FU in treatment of recalcitrant palmo-plantar warts however much more side effects were noted in intralesional bleomycin than intralesional 5-FU. None of the side-effects were found to be life threatening. Moreover 5-FU is cheaper and easily procurable than injection bleomycin. Conclusion: Both intralesional bleomycin and 5-FU injections can be safely used in the treatment of recalcitrant palmo-plantar verrucae.